2004
DOI: 10.1093/intqhc/mzh032
|View full text |Cite
|
Sign up to set email alerts
|

Using clinical indicators in a quality improvement programme targeting cardiac care

Abstract: Use of clinical indicators succeeded in supporting clinicians to monitor practice standards and to realize change in systems of care and clinician behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 27 publications
2
38
0
1
Order By: Relevance
“…Two articles reporting on the same study but providing different outcomes were abstracted for this analysis. 42,43 There were 7 disagreements among the reviewers about eligibility of the studies, leading to a value of 0.76. All disagreements were resolved by consensus.…”
Section: Resultsmentioning
confidence: 99%
“…Two articles reporting on the same study but providing different outcomes were abstracted for this analysis. 42,43 There were 7 disagreements among the reviewers about eligibility of the studies, leading to a value of 0.76. All disagreements were resolved by consensus.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies showed that the use of indicators and quality programs significantly improve the quality of health care [62,63]. Monitoring indicators implies an administrative burden for physicians and should be worth the effort.…”
Section: Discussionmentioning
confidence: 99%
“…These efforts resulted in increased accessibility of hospital emergency departments and greater efficiency of acute and long-term care. Another study developed and reported clinical indicators as measures of the quality of care received by patients with acute coronary syndromes or congestive heart failure [63]. The study showed that clinical indicators can be used by clinicians to monitor practice standards and to effectuate change in system of care and clinician behavior.…”
Section: Discussionmentioning
confidence: 99%
“…The ideal number of measures represents a balance between having too few (leading to over-emphasis on some aspects of care and neglect of others) and too many (causing confusion and administrative overload). Process-ofcare indicators which, in the main, comprise proportions of eligible patients who receive specific interventions, must be rigorously developed and tested using accepted methods, 35 based on current evidence, and rapidly responsive to changes in guidelines and professional consensus. They should incorporate standard data definitions which are recognised by relevant professional organisations.…”
Section: Principle 2 Use Established Evidence-based Performance Measmentioning
confidence: 99%